1994
DOI: 10.1038/367554a0
|View full text |Cite|
|
Sign up to set email alerts
|

Parasitism, mutation accumulation and the maintenance of sex

Abstract: Two classes of models attempt to explain why obligate partheno-genesis only rarely replaces sexual reproduction in natural populations, in spite of the apparent reproductive advantage that parthenogens gain by producing only female offspring. The mutation-accumulation models suggest that sex is adaptive because it purges the genome of harmful recurrent mutations. The ecological genetic models postulate that sex is adaptive in variable environments, particularly when the relevant variation is generated by coevo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
251
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 315 publications
(267 citation statements)
references
References 9 publications
16
251
0
Order By: Relevance
“…Previous studies using this system have demonstrated that phages can reduce bacterial withinpopulation diversity (Buckling & Rainey 2002b;Brockhurst et al 2004), but given the massive bacterial population sizes (approximately 10 9 ) and that colony morphological variation was detected in the majority of samples of only 100 individuals, it is unlikely that population bottlenecks would be sufficiently small. Note that this acceleration of Muller's ratchet resulting from coevolution with parasites has been invoked to explain the evolutionary advantage of sexual over asexual reproduction (see below), as sexual reproduction will allow the production of offspring with lower mutational loads than their parents (Howard & Lively 1994 Finally, we cautiously extrapolate the results from this study to the evolutionary maintenance of sexual reproduction, as have several previous studies dealing with asexual organisms (Elena & Lenski 1997;Cooper et al 2005). There are currently two major hypotheses to explain why sexual reproduction might have a selective advantage over asexual reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies using this system have demonstrated that phages can reduce bacterial withinpopulation diversity (Buckling & Rainey 2002b;Brockhurst et al 2004), but given the massive bacterial population sizes (approximately 10 9 ) and that colony morphological variation was detected in the majority of samples of only 100 individuals, it is unlikely that population bottlenecks would be sufficiently small. Note that this acceleration of Muller's ratchet resulting from coevolution with parasites has been invoked to explain the evolutionary advantage of sexual over asexual reproduction (see below), as sexual reproduction will allow the production of offspring with lower mutational loads than their parents (Howard & Lively 1994 Finally, we cautiously extrapolate the results from this study to the evolutionary maintenance of sexual reproduction, as have several previous studies dealing with asexual organisms (Elena & Lenski 1997;Cooper et al 2005). There are currently two major hypotheses to explain why sexual reproduction might have a selective advantage over asexual reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…whether this meiotic drive increases the zygote's fitness or is just a 'curious side-effect of a curious gene' (Pomiankowski & Hurst, 1993). In the case of the MHC, however, choosing for optimal allele combinations during fertilization could be adaptive, as it allows for a rapid response to the very important selection pressure by infectious diseases. One of the most substantial benefits of sexual reproduction itself could be that it allows to react to the continuously changing selection pressure induced by infectious diseases (Hamilton et a!., 1990, Howard & Lively, 1994. This counteraction…”
Section: Discussionmentioning
confidence: 99%
“…The benefits of being adapted to infect local hosts are substantial, much like the costs of failure. This is a requirement for parasites to evolve with host populations, and particularly to maintain sexual reproduction [5,7,10,26]. The first column represents the 'field parasite' treatment, where snails (host 1) were exposed to parasites from waterfowl faeces collected from the field.…”
Section: Discussionmentioning
confidence: 99%